2019
DOI: 10.1021/acs.jpcb.9b07526
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Unusually High Fluorescence Anisotropy of 3-Hydroxyflavone in Water: Formation of Probe–Solvent Cage-like Cluster

Abstract: Based on the unusually high fluorescence anisotropy (FA) of 3-hydroxyflavone (3HF) in water medium in contrast to the very low FA of its methoxy counterpart (3MF), our proposition invoked formation of an intermolecular hydrogen-bonded cage-like probe–solvent cluster of 3HF in water. In the present work, ab-initio DFT-based quantum chemical calculations have been exploited to provide a foundation for our interpretation. Ground-state optimization of 3HF with varying numbers of water molecules leads to the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…But the excitation spectrum performed at 496 nm (Figure 4) evidenced that the origin of the fluorescence was not the fully protonated morin (absorption maximum at 357 nm) but another species absorbing at 423 nm. Supported by the two former works, [11,46] by the fact that the fully protonated morin was virtually not fluorescent and by the excitation spectrum, we put forward the hypothesis that the fluorescence centred at 500 nm for a pH 2.01 (and more generally in acidic MeOH) was coming from a solvated neutral morin-MeOH intermolecular H-bonded cage-like complex.…”
Section: Steady-state Spectroscopymentioning
confidence: 83%
See 1 more Smart Citation
“…But the excitation spectrum performed at 496 nm (Figure 4) evidenced that the origin of the fluorescence was not the fully protonated morin (absorption maximum at 357 nm) but another species absorbing at 423 nm. Supported by the two former works, [11,46] by the fact that the fully protonated morin was virtually not fluorescent and by the excitation spectrum, we put forward the hypothesis that the fluorescence centred at 500 nm for a pH 2.01 (and more generally in acidic MeOH) was coming from a solvated neutral morin-MeOH intermolecular H-bonded cage-like complex.…”
Section: Steady-state Spectroscopymentioning
confidence: 83%
“…Another recent work combining experiments and theoretical quantum chemical calculations brought new insights about the origins of the LW absorption band of 3HF: Chattopadhyay et al evidenced that in protic solvents, especially in water, 3HF exhibited a high fluorescence anisotropy contrarily to 3-methoxyflavone. [46] In nonpolar aprotic solvents, they observed that the fluorescence anisotropy of 3HF was low. Using ab-initio quantum chemical calculations, they found that 3HF formed a solvated cluster in aqueous solution.…”
Section: Steady-state Spectroscopymentioning
confidence: 99%
“…It is suspected that 3HF forms a stable complex with the solvent, of red-shied absorption energy compared to the lone neutral 3HF, explaining the high dependence on the medium of the emission. [69][70][71] Most research groups concluded however on the emission from the anion aer an ESPT (intermolecular) to the solvent. [72][73][74][75] The situation is more complicated in the case of 2 0 3HF, as band X and A are very different in intensities, energies and shape, a result that cannot be explained currently.…”
Section: Excited-statementioning
confidence: 99%
“…3HF exhibits ESIntraPT and gives dual fluorescence corresponding to its E* and K* forms with a large Stokes shift and photostability [28][29][30]. Thus, 3HF has been used as a prototype for the ESIntraPT processes and as sensitive fluorescence probes for discovering binding sites in various bio-relevant targets such as DNA, protein, and biomembranes [31][32][33]. The photophysical properties and ESPT processes of 3HF in organic solvents have been extensively studied [34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%